HBeAg Seroconversion in HBeAg-Positive Chronic Hepatitis B Patients Receiving Long-Term Nucleos(t)ide Analog Treatment: A Systematic Review and Network Meta-Analysis. - Tongjing Xing; Hongtao Xu; Lin Cao; Maocong Ye (PLoS ONE, 2017)
Background HBeAg seroconversion is an important intermediate outcome in HBeAg-positive chronic hepatitis B (CHB) patients. This study aimed to compare the effect of nucleos(t)ide analogs (NAs) on HBeAg seroconversion in treating CHB with lamivudine, adefovir, telbivudine, entecavir, and tenofovir. Methods Network meta-analysis of NA treatment-induced HBeAg seroconversion after 1-2 years of treatment was performed. In addition, NA treatment-induced HBeAg seroconversion after 3-5 years of treatment was systematically evaluated. Results A total of 31 articles were included in this study. Nine and five studies respectively reporting on 1- and 2-year treatment were included in our network meta-analysis. In addition, 6, 5, and 5 studies, respectively reporting on 3-, 4-, and 5-year treatment were included in our systematic evaluation. Telbivudine showed a significantly higher HBeAg seroconversion rate after a 1 year treatment period compared to the other NAs (odds ratio (OR) = 3.99, 95% CI 0.68-23.6). This was followed by tenofovir (OR = 3.36, 95% CI 0.70-16.75). Telbivudine also showed a higher seroconversion rate compared to the other NAs after a 2 year treatment period, (OR = 1.38, 95% CI 0.92-2.22). This was followed by entecavir (OR = 1.14, 95% CI 0.72-1.72). No significant difference was observed between spontaneous induction and long-term telbivudine treatment-induced HBeAg seroconversion. However, entecavir and tenofovir treatment-induced HBeAg seroconversions were significantly lower than spontaneous seroconversion. Conclusion Long-term treatment with potent anti-HBV drugs, especially tenofovir and entecavir, may reduce HBeAg seroconversion compared with spontaneous HBeAg seroconversion rate. Telbivudine treatment, whether short term or long term, is associated with higher HBeAg seroconversion compared with the other NAs. However, the high rates of drug resistance likely limit the application of telbivudine.